Perbandingan Biaya dan Waktu Pelaksanaan pada Lokasi Pembangunan LRT Jakarta Fase 1B Antara Metode Kerja Pemasangan Rebar Joint Coupler Prafabrikasi dengan Metode Kerja Pemasangan Rebar Tanpa Joint Coupler di Fabrikasi - Irwan Fikri; Moh. Azhar; Pio Ranap Tua Naibaho (Jurnal Talenta Sipil, 2026)
Population growth and high economic activity in the DKI Jakarta area have led to a significant increase in vehicle volume and traffic congestion. These conditions require an efficient, safe, and environmentally friendly mass transportation system in order to reduce the public's dependence on private vehicles. One of the national strategic projects designed to address this challenge is the construction of the Jakarta Light Rail Transit (LRT) Phase 1B. In the construction of the LRT, time and cost efficiency are crucial factors that determine the success of the project. This study aims to analyze and compare the efficiency of two methods of installing steel reinforcement (rebar), namely the prefabricated joint coupler system and the conventional method without couplers. The study uses a quantitative descriptive approach by collecting secondary data in the form of Unit Price Analysis (AHSP), project progress reports, and field observations. The analysis was conducted on labor productivity, material costs, and implementation time. The results showed that the rebar installation method with prefabricated joint couplers was able to save 15-20% of steel material, reduce the duration of work by around 25-30%, and significantly reduce labor costs compared to the conventional method. In addition, the prefabrication system provides more consistent work quality, minimizes the risk of delays, and improves work safety. Based on these results, it is concluded that the application of the prefabricated joint coupler method is more effective and efficient in both technical and economic aspects for the Jakarta LRT Phase 1B construction project and can be recommended for similar infrastructure projects in the future.